Highly dependable software - Zelkowitz, Marvin V., 1945- (Amsterdam ; Boston : Academic Press, 2003)
Since 1960, Advances in Computers has chronicled the constantly shifting theories and methods of Information Technology which greatly shapes our lives today. Highly Dependable Software is the 58th volume in this Series. The seven chapters describe various approaches towards dependability: software development measurability, transformation oriented programming, Bounded Model Checking, GUI testing, history and lessons from software inspections, impact and problems related to errors in software, the evolution of the various security policies. This book would be an invaluable addition to any university course in computer technology, and an excellent reference tool for industrial practitioners. * Includes in-depth surveys and tutorials on advances in Computer Technology.* Features the work of well-known authors and researchers in the field.* Provides a broad overview of important developments.* Contains extensive bibliographies.
Preface. -- Contributors. -- Software development productivity, K.D. Maxwell. -- Transformation-oriented programming: A development methodology for high assurance software, V.L. Winter, S. Roach and G. Wickstrom. -- Bounded model checking, A. Biere, A. Cimatti, E.M. Clarke, O. Strichman and Y. Zhu. -- Advances in GUI testing, A.F. Memon. -- Software inspections, M. Roper, A. Dunsmore and M. Wood. -- Software fault tolerance forestalls crashes: To err is human, to forgive is fault tolerant, L. Bernstein. -- Advances in the provisions of system and software security -- Thirty years of progress, R.B. Vaughn.
Includes bibliographical references and index.
Keywords: Computer software; Reliability (Engineering).; Logiciels; Electronic books